2006
DOI: 10.1155/ijrm/2006/79084
|View full text |Cite
|
Sign up to set email alerts
|

Clearance Analysis and Leakage Flow CFD Model of a Two‐Lobe Multi‐Recompression Heater

Abstract: This paper reports the results of a study on multi-recompression heating. This process employs a Roots-type mechanism to heat gases to very high temperatures by compressive gas heating. A CFD model predicting the leakage flows in the machine was developed, and an excellent comparison with experimental data taken on a two-lobe Roots blower was obtained. A "clearance analysis" was performed to show that the clearance between the impellers remains constant for 96% of the angles of rotation. Assuming a quasi-stead… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 0 publications
0
22
0
Order By: Relevance
“…Considering the compressing process in the outlet chamber, from [17], the relation between temperature and pressure are given by the following set of equations: (14) substituting (11,12,13) into (14), we can calculate the temperature of the outlet chamber:…”
Section: Casementioning
confidence: 99%
See 1 more Smart Citation
“…Considering the compressing process in the outlet chamber, from [17], the relation between temperature and pressure are given by the following set of equations: (14) substituting (11,12,13) into (14), we can calculate the temperature of the outlet chamber:…”
Section: Casementioning
confidence: 99%
“…The results of the research [8] showed that the performance of blower decreased 43 % when the clearance dimension was 2.0 mm. Ashish et al [11] have investigated and evaluated the phenomenon of leakage of the Roots compressor with the involute rotor profile. Based on survey of those researches, we can see most of the works have implied CFD and experimental method, and the theoretical method was rarely used due to the complexity of Roots profile and due to the fact that the clearances (the clearance between two rotors in matching process K  and the clearances between rotor and stator r  ) significantly affect on performance of the blower.…”
Section: Introductionmentioning
confidence: 99%
“…Xing et al [19] used TwinMesh and ANSYS-CFX to simulate a three-lobe Roots blower numerically and display the presence of strong vorticial flow field and backflow through three gaps. Joshi et al [20] predicted the leakage flow rate in a two-lobe Roots blower using a stationary mesh in CFD at a single rotation angle and compared them with experimental data. A tip step which was also applied in the present study was used and was proved to reduce tip leakage of the Roots blower [20].…”
Section: Introductionmentioning
confidence: 99%
“…Li, Jia, Meng, Shen, and Sang (2013) analysed the effects of different pressure angles on the velocity and pressure of oil as well as the turbulent kinetic energy by 2D numerical modeling. Joshi, Blekhman, Felske, Lordi, and Mollendorf (2006) analysed the clearance between the rotors, showing that the clearance remains constant for 96% of the angles of the rotation in a working period. They also investigated the leakage of the Roots blower through a quasi-steady state analysis.…”
Section: Introductionmentioning
confidence: 99%